(untitled) (LEARNing Landscapes, 2014)
This article summarizes research conducted by a teacher researcher in a workingclass community. The participants included 10 Latino students, five parents, and five teachers. This qualitative study utilized narrative inquiry to construct the stories of all 20 participants in order to investigate how funds of knowledge is perceived, interpreted, and used by students, parents, and teachers in this high school community. Interviews, observations, document analysis, and photovoice journals were used to gather data. Findings indicated that teachers perceived funds of knowledge differently than students and their parents, which may result in a loss of instructional opportunities.